2019
DOI: 10.1038/s41467-019-09394-5
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed nickel–nitrogen–sulfur species anchored on porous carbon nanosheets for efficient water oxidation

Abstract: Developing low-cost electrocatalysts to replace precious Ir-based materials is key for oxygen evolution reaction (OER). Here, we report atomically dispersed nickel coordinated with nitrogen and sulfur species in porous carbon nanosheets as an electrocatalyst exhibiting excellent activity and durability for OER with a low overpotential of 1.51 V at 10 mA cm −2 and a small Tafel slope of 45 mV dec −1 in alkaline media. Such electrocatalyst represents the best among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
282
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 475 publications
(299 citation statements)
references
References 60 publications
4
282
1
Order By: Relevance
“…[40,41] The N 2 adsorption/desorption isotherm experiments show that the content of Fe has a significant effect on the porosity of the resulting carbon structures. [43,44] The above results reinforce the important role of the formation of dual Fe-Co sites in favoring the rate-limiting OH − activation for OER. By increasing the Fe content, the Brunauer-Emmett-Teller (BET) surface area gradually decreases from 455 (Co@CC) to 375 (CoFe5 CC) and 298 m 2 g −1 (CoFe10@CC).…”
supporting
confidence: 68%
“…[40,41] The N 2 adsorption/desorption isotherm experiments show that the content of Fe has a significant effect on the porosity of the resulting carbon structures. [43,44] The above results reinforce the important role of the formation of dual Fe-Co sites in favoring the rate-limiting OH − activation for OER. By increasing the Fe content, the Brunauer-Emmett-Teller (BET) surface area gradually decreases from 455 (Co@CC) to 375 (CoFe5 CC) and 298 m 2 g −1 (CoFe10@CC).…”
supporting
confidence: 68%
“…To further improve the OER performance of Ni‐based SACs, coordinated‐S atoms have been introduced to modify local electronic structures. Hou et al reported atomically dispersed Ni atoms on N and S codoped porous carbon supports (S|NiN x ‐PC/EG) (Figure i) . According to the calculated formation energy and OER overpotentials for different models, the NiN 3 S configuration was predicted to be the best active site.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis For mentioning
confidence: 97%
“…Heteroatom doping involves the substitution of carbon atoms within the carbon skeleton. Heteroatoms with a different size and electronegativity induce a charge redistribution at the metal center by either directly acting as a coordination atom (e.g., PtS 4 or NiN 3 S) or modulating the long‐range electronic structure of the support …”
Section: Engineering Sacs On Carbon‐based Substratesmentioning
confidence: 99%
“…The active sites of AD‐Sn/N‐C were believed to be Sn–N x , which was similar to other M–N x structure. In addition to the well‐developed M–N x moiety, the transition metal atoms coordinated with N, S, and Cl atoms are stimulated to serve as the active sites of carbon‐rich NPMSACs, such as M–N x S y moiety or M–N x Cl y moiety. For instance, the S and N atoms were introduced on the electrochemically exfoliated graphene by high‐temperature pyrolysis treatment of dicyandiamide‐ and thiophene‐based precursors, where the two precursors were assembled with transition metal salt at a molecular scale via hydrothermal reaction and further converted to N/S‐codoped Ni‐based SAC …”
Section: Carbon‐rich Npmsacs For Crr and Hermentioning
confidence: 99%